Mnk1 is a novel acinar cell-specific kinase required for exocrine pancreatic secretion and response to pancreatitis in mice. Issue 6 (18th July 2014) - Cendrowski, Jaroslaw; Lobo, Víctor J Sánchez-Arévalo; Sendler, Matthias; Salas, Antonio; Kühn, Jens-Peter; Molero, Xavier; Fukunaga, Rikiro; Mayerle, Julia; Lerch, Markus M; Real, Francisco X
Abstract : Objective: Pancreatic acinar cell maturation is dependent on the activity of the pancreas transcription factor 1 (PTF1) complex. Induction of pancreatitis leads to MAP kinase activation and transient suppression of the acinar differentiation programme. We investigated the role of MAP kinase-interacting kinase 1 (Mnk1) in mouse exocrine pancreas development and in the response to secretagogue-induced pancreatitis. Design: Mnk1 expression was analysed using immunohistochemistry, RT-qPCR and western blotting. Ptf1a binding to Mnk1 was assessed by chromatin immunoprecipitation and qPCR. Acute pancreatitis was induced in wild type and Mnk1 −/− mice by 7 h intraperitoneal injections of caerulein. In vitro amylase secretion and trypsinogen activation were assessed using freshly isolated acinar cells. In vivo secretion was quantified by secretin-stimulated MRI. Results: Mnk1 is expressed at the highest levels in pancreatic acinar cells and is a direct PTF1 target. Mnk1 is activated upon induction of pancreatitis and is indispensable for eIF4E phosphorylation. The pancreas of Mnk1 −/− mice is histologically normal. Digestive enzyme content is significantly increased and c-Myc and Ccnd1 levels are reduced in Mnk1 −/− mice. Upon induction of acute pancreatitis, Mnk1 −/− mice show impaired eIF4E phosphorylation, activation of c-Myc and downregulation of zymogen content. Acinar cells show defective relocalisation of digestive enzymes, polarity defects and impaired secretory response in vitro and in vivo. Conclusions: Mnk1 is a novel pancreatic acinar cell-specific stress response kinase that regulates digestive enzyme abundance and eIF4E phosphorylation. It is required for the physiological secretory response of acinar cells and for the homeostatic response to caerulein administration during acute pancreatitis.